Safety and Efficacy of Ferric Carboxymaltose in Anemic Pregnant Women: A Retrospective Case Control Study. (24th November 2015) - Pels, Anouk; Ganzevoort, Wessel
Abstract : Background . Anemia during pregnancy is commonly caused by iron deficiency and can have severe consequences for both the mother and the developing fetus. The aim of this retrospective study was to assess the safety and efficacy of intravenous ferric carboxymaltose (FCM) in pregnant women. Methods . All women treated with FCM for anemia during pregnancy between 2010 and 2012 at our institution were included. A matched control group was selected, including women who either were nonanemic or had anemia but were not considered for intravenous iron. Main outcome measures were maternal safety and pregnancy outcomes. Results . The study included 128 patients (FCM: 64; control: 64). Median FCM dose was 1000 mg and median gestational age at the time of first treatment was 34 weeks and 6 days. Median Hb increased from 8.4 g/dL (interquartile range 7.7; 8.9 g/dL) at the first FCM administration to 10.7 g/dL (9.8; 11.5 g/dL;n = 46 with available Hb at delivery) at the time of delivery, achieving levels similar to those in the control group (10.8 g/dL [9.8; 11.8 g/dL;n = 48 ]). No treatment-related adverse events were reported and no statistically significant differences in pregnancy outcomes were observed between groups. Conclusions . Within the limitations of this case control study, FCM was a safe and efficient treatment of anemia during pregnancy.